Pengaruh Intensitas Modal, Pertumbuhan Penjualan Dan Kompensasi Eksekutif Terhadap Penghindaran Pajak (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2018 – 2020) - Firdaus, Vidella Anisa; Poerwati, Rr Tjahjaning (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2022)
This study aims to examine the effect of capital intensity, sales growth and executive compensation on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange for the period 2018 – 2020. Determine the number of samples using the purposive sampling method in order to obtain 44 companies. The method used is panel data regression with a fixed effect model (FEM). The results showed that capital intensity had a significant positive effect on tax avoidance. Whereas sales growth and executive compensation have no effect on tax avoidance.